Highly electro-responsive plasticized PVC/FMWCNTs soft composites: A novel flex actuator with functional characteristics. (5th March 2020) - Ali, Imdad; Yang, Weimin; Li, Xudong; Ali, Ahsan; Jiao, Zhiwei; Xie, Pengcheng; Dias, Otavio Augusto Titton; Pervaiz, Muhammad; Li, Haoyi; Sain, Mohini
Graphical abstract: Highlights: Functional MWCNTs/PVC soft composites based flexible actuator has been fabricated. A novel physicochemical mechanism of PVC/FMWCNTs composites has been proposed. The maximum deformation observed was 34% under a given applied voltage in 0.1 s. High deformation of the composite was associated with dispersion quality of FMWCNTs. The soft composites demonstrated good thermal stability and higher strain about 500%. Abstract: Electro-responsive devices are used in actuators and artificial muscles but susceptible low deformation limits its applications. Herein, we prepared soft composites from functional multi-wall carbon nanotubes (FMWCNTs) and plasticized polyvinyl chloride (PVC). The PVC/FMWCNTs soft composite assembled with double layer electrodes functioned as a highly flexible contraction actuator. Furthermore, the chemical structure and surface morphology of the PVC/FMWCNTs composites are characterized by using FT-IR, Raman, XRD, and SEM techniques. The deformation of an optimized soft composite in the designed device is found to be 34% under a specified applied voltage. To the best of our knowledge, this contraction deformation value based on flexible PVC/FMWCNTs soft composites is the highest reported value to date. Moreover, the incorporation of FMWCNTs in plasticized PVC resulted in a high elongation at break of about 500%. The obtained results strongly indicated that the electro-stimulated soft composites have promising applications in soft wearable devices, actuators and artificial muscles.